2016
DOI: 10.1007/s10508-016-0884-2
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Kin-Directed Altruism Emerges in Childhood and Is Linked to Feminine Gender Expression in Samoan Fa’afafine: A Retrospective Study

Abstract: Androphilia refers to sexual attraction toward adult males, whereas gynephilia refers to sexual attraction toward adult females. The kin selection hypothesis posits that androphilic males help kin increase their reproductive output via kin-directed altruism, thus offsetting their own lowered reproduction and contributing to the fitness of genes underpinning male androphilia. Support for this hypothesis has been garnered in several Samoan studies showing that feminine androphilic males (known locally as fa'afaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Research conducted on cisgender androphilic males in industrialized cultures has provided little support for the KSH [ 2 , 54 58 ]. In contrast, research conducted on transgender androphilic males in Samoa has repeatedly found support for the KSH by means of elevated kin directed altruism among fa’afafine [ 59 64 ]. Because the transgender form of male androphilia appears to be ancestral to the cisgender form [ 65 ], the former likely represents a better model when testing evolutionary hypotheses pertaining to male androphilia than the later.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted on cisgender androphilic males in industrialized cultures has provided little support for the KSH [ 2 , 54 58 ]. In contrast, research conducted on transgender androphilic males in Samoa has repeatedly found support for the KSH by means of elevated kin directed altruism among fa’afafine [ 59 64 ]. Because the transgender form of male androphilia appears to be ancestral to the cisgender form [ 65 ], the former likely represents a better model when testing evolutionary hypotheses pertaining to male androphilia than the later.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that fa'afafine's altruistic tendencies toward nieces and nephews are significantly elevated compared to those of Samoan women (Vasey and VanderLaan 2009) and gynephilic men VanderLaan et al 2017;Vasey et al 2007;Vasey and VanderLaan 2010a). These tendencies manifest behaviourally in terms of increased allocation of money by fa'afafine to their youngest sibling's daughters (Vasey and VanderLaan 2010b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Here and elsewhere, the correlation between androphilia and femininity is easily read as fundamentally causal. The authors categorise fa'afāfine as “male” when testing their participants' sexual orientation using the Kinsey scale (Bartlett & Vasey, ; Vasey & Vanderlaan, ) and also describe masculine men who have sexual relations with fa'afāfine as to some extent androphilic—although fa'afāfine's masculine sexual partners are referred to as “straight” by Samoans, the group suggest that “straight man” has quite a different meaning in Samoa than in Western contexts because these men have sex with fa'afāfine (Vanderlaan, Petterson, & Vasey, ). It seems that ultimately these researchers see fa'afāfine as “men,” regardless of how they are understood within the Samoan sexual schema.…”
Section: Essentialising Homosexualitymentioning
confidence: 99%
“…Here, I wish to focus on the exploration of fa'afāfine's “avuncularity” (how they behave as “uncles”) . These discussions are founded in the evolutionary puzzle supposedly posed by androphilia, which is assumed to be a genetic trait but is also an evolutionary “dead end” because of the apparent lack of reproductive potential (Vanderlaan et al, ). Thus, the continued existence of androphilia requires an evolutionary explanation (Vasey & Vanderlaan, ; Vanderlaan & Vasey, ).…”
Section: Functionalist Approachesmentioning
confidence: 99%
See 1 more Smart Citation